Electrochemical purification method for natural graphite spherical tailings
Through ultrasonic acid leaching and electrolysis treatment of natural graphite spherical tailings, the toxicity and pollution problems of leaching reagents in the impurity removal process in the existing technology are solved, and the purification of high-purity graphite is achieved, which is suitable for the field of lithium-ion batteries.
Patent Information
- Application Number
- CN202411351904.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-21
AI Technical Summary
When removing impurities from natural graphite, the leaching reagents used in the prior art are highly toxic and corrosive, and are prone to pollute the environment. The fixed carbon content of purified graphite is usually less than 99.9%, making it difficult to be applied in the field of lithium-ion batteries.
Using an electrochemical purification method of natural graphite spherical tailings, through ultrasonic acid leaching and electrolysis treatment, using an electrolyte composed of deionized water, acid and hydrofluoric acid, an ultrasonic acid leaching and a second electrolytic acid leaching are performed to prepare high-quality Pure graphite.
It effectively reduces the usage of hydrofluoric acid and reduces environmental pollution. The purity of the purified graphite product reaches 99.9% or above, which is suitable for lithium-ion battery negative electrode materials.
Smart Images

Figure CN119330350A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of secondary resource utilization, and in particular to an electrochemical purification method for natural graphite spherical tailings. Background Art
[0002] Natural graphite is one of the allotropes of carbon. It is mainly composed of carbon atoms arranged in a hexagonal layer structure. Each carbon atom forms a six-membered ring through covalent bonds, forming a layered structure of graphite. The weak van der Waals force between these layers makes graphite have good flexibility and lubricity. At the same time, the carbon atoms in the layer are arranged in sp 2 The hybrid orbital forms a σ bond, which gives graphite good electrical conductivity and has great application potential as a negative electrode material for lithium-ion batteries. However, in nature, natural graphite usually exists in the form of ore, the main component of which is graphite, but it also contains a certain proportion of other elements and impurities, which may be introduced by contact with other minerals or chemical reactions during the formation of graphite. The main impurity elements in natural graphite include silicon (Si), aluminum (Al), iron (Fe), calcium (Ca), magnesium (Mg), etc. These impurities usually exist in the form of oxides or sulfides, embedded in the graphite surface and carbon layer, and tightly combined with the carbon matrix, making it difficult to separate and purify. The presence of impurities will affect the physical and chemical properties of graphite. Therefore, it is of great significance to find energy-saving, environmentally friendly, and high-speed purification technologies for producing high-purity graphite using natural graphite as raw material.
[0003] At present, many technologies have been developed and applied to remove impurities from natural graphite. Commonly used methods include flotation, alkali-acid method, chloride roasting method, high-temperature purification method, and hydrofluoric acid method. The grade of natural graphite purified by flotation can only reach a certain range, because some impurities are in extremely fine particles impregnated in graphite flakes, and even fine grinding cannot completely dissociate the monomers. Therefore, it is difficult to completely remove these impurities by flotation method, and it is generally only used as the first step in graphite purification. Although the alkali-acid method can greatly improve the purity and has the advantages of simple equipment and strong versatility, it has high production costs, large graphite loss, serious water pollution, and more importantly, it will destroy the structure of graphite. The chloride roasting method has the advantages of energy saving, high purification efficiency (>98%), and high recovery rate. However, factors such as the toxicity, severe corrosiveness and severe environmental pollution of chlorine have limited the promotion and application of the chloride roasting method to a certain extent. The high-temperature purification method can produce ultra-high purity graphite of more than 99.99%, but it requires that the fixed carbon content of the raw material be more than 99%. In addition, the equipment is expensive, the investment is huge, and the production scale is limited. The electric furnace heating technology has strict requirements and needs to be isolated from the air. Otherwise, the graphite will begin to be oxidized when the temperature rises to 450°C in the hot air. The higher the temperature, the greater the loss of graphite.
[0004] The hydrofluoric acid method for purifying graphite is a common graphite purification technology, which mainly purifies graphite by reacting hydrofluoric acid with impurities in graphite. When elements such as Ca, Mg, and Fe are present, insoluble CaF2, MgF2, and FeF3 will be generated, resulting in reduced purification efficiency, so pretreatment is required. The hydrofluoric acid method has the advantages of good purification effect, strong processing capacity, and simple operation, but hydrofluoric acid is highly toxic. If used in large quantities, a large amount of fluorine-containing sludge will be formed during the waste liquid treatment process, causing serious environmental pollution. Therefore, it is necessary to reduce the use of hydrofluoric acid.
[0005] In summary, the existing technology for removing impurities from natural graphite has highly toxic and corrosive leaching reagents, which easily pollute the environment. In addition, the fixed carbon content of the purified graphite is usually less than 99.9%, which makes it difficult to further apply it to the field of lithium-ion batteries.
[0006] Therefore, there is an urgent need to provide a method for electrochemical purification of natural graphite spherical tailings to solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings and defects of the prior art and provide a method for electrochemically purifying natural graphite spherical tailings, which effectively reduces the amount of hydrofluoric acid used, is beneficial to environmental protection, and the purity of the purified graphite product is as high as 99.9% or above.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A method for electrochemically purifying natural graphite spherical tailings comprises the following steps:
[0010] Step 1, dispersing the dried natural graphite spherical tailings in a solvent consisting of deionized water and acid at a certain solid-liquid ratio to form a suspension, and subjecting the suspension to an ultrasonic-assisted acid leaching treatment for a certain period of time;
[0011] Step 2, filtering the suspension, collecting the graphite sample after acid leaching, drying the graphite sample, and then pressing the dried graphite sample into sheets;
[0012] Step 3, electrolyzing the graphite sample obtained in step 2, wherein the electrolyte is a mixed solution composed of hydrofluoric acid, sulfuric acid and deionized water. After the electrolysis is completed, filtering and separating the electrolyte and the graphite sample is performed, and then the graphite sample is dried, and finally the dried graphite sample is subjected to quality inspection.
[0013] As a preferred technical solution of the present invention, the particle size of the natural graphite spherical tailings used in step 1 is 5 to 15 μm.
[0014] As a preferred technical solution of the present invention, the solid-liquid ratio of the natural graphite spherical tailings to the solution in step 1 is one of 1:4, 1:5, and 1:6.
[0015] As a preferred technical solution of the present invention, in step 1, the acid of the solvent is one of hydrochloric acid, hydrofluoric acid and sulfuric acid, or a mixture of two or more thereof, and the ratio of the acid to deionized water is one of 1:1, 1:2 and 2:3.
[0016] As a preferred technical solution of the present invention, in step 1, the ultrasonic assisted acid leaching time is 4 to 8 hours and the temperature is 40 to 70°C.
[0017] As a preferred technical solution of the present invention, the pressure of the graphite sample in step 2 is 30 MPa, and the diameter of the graphite sheet after forming is 1.8 cm.
[0018] As a preferred technical solution of the present invention, the ratio of hydrofluoric acid, sulfuric acid and deionized water in the electrolyte used in step 3 is (3-6): (5-8): (26-32).
[0019] As a preferred technical solution of the present invention, the electrolysis temperature in step 3 is 20°C to 90°C, the solid-liquid ratio of the graphite sample to the electrolyte is 1:(10-4) and the electrolysis time is 2 to 12 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention uses spherical graphite tailings as raw materials, prepares high-purity graphite through primary ultrasonic acid leaching and secondary electrolytic acid leaching, effectively reduces the use of hydrofluoric acid, and is beneficial to environmental protection. The method has low preparation cost, simple operation method, low energy consumption, and is easy to prepare on a large scale. The purity of the purified graphite product is as high as 99.9% or more, and can be applied to the field of negative electrode materials for lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0024] The present invention provides a method for electrochemical purification of natural graphite spherical tailings, combining the purification and exfoliation of spherical graphite tailings with optimized electrolyte formulation and voltage control. An electrochemical purification mechanism is proposed in which the graphite layer expands to expose and separate non-graphite minerals, promotes the exfoliation of the graphite layer to remove non-graphite minerals, and finally dissolves and precipitates non-graphite minerals. The purified products are graphene and graphite aggregates, and the minimum amount of hydrofluoric acid required to obtain 99.9% high-purity graphite is studied. The obtained high-purity graphite is used in the preparation of lithium battery anodes, and the effect of the purification process on the performance of lithium battery anodes is verified through performance testing.
[0025] The specific implementation process of the present invention is as follows:
[0026] like Figure 1 As shown, a method for electrochemical purification of natural graphite spherical tailings comprises the following steps:
[0027] In the first step, impurities such as metal oxides and silicates in natural graphite spherical tailings are removed by acid leaching. Specifically, the dried natural graphite spherical tailings are dispersed in a solvent composed of deionized water and acid at a certain solid-liquid ratio to form a suspension, and the suspension is acid-leached for a certain period of time under the assistance of ultrasound.
[0028] The second step is to separate the graphite particles from the solution after acid leaching in the first step, and dry and shape them. Specifically, the suspension is filtered, the graphite samples after acid leaching are collected, the graphite samples are dried to remove residual water, and the dried graphite samples are pressed into sheets for subsequent electrolytic treatment.
[0029] The third step is to further purify the graphite obtained in the second step by electrolysis to prepare a 99.9% high-purity natural graphite material suitable for lithium-ion batteries. Specifically, an electrolyte suitable for electrolysis is prepared, and the graphite sample obtained in the second step is placed in an electrolytic cell, the power is turned on, and the electrolysis treatment is started. After the electrolysis is completed, the electrolyte is separated from the graphite sample. Impurities and residues in the electrolyte are removed by filtration, and the purified graphite sample is collected. The collected graphite samples are dried to remove residual moisture and solvents. Finally, the dried graphite samples are subjected to quality inspection, including purity testing, particle size analysis, etc., to ensure that they meet the quality standards of 99.9% natural graphite materials for lithium-ion batteries.
[0030] The present invention uses spheroidized graphite tailings as raw materials, develops a graphite green industry, and prepares 99.9% high-purity graphite through primary ultrasonic acid leaching and secondary electrolytic acid leaching. The primary acid leaching is to immerse the graphite in a hydrochloric acid solution and ultrasonically assist the leaching; the secondary electrolysis is to press the graphite treated by the primary acid leaching into a sheet as a positive electrode, a platinum sheet as a negative electrode, sulfuric acid, hydrofluoric acid and deionized water as electrolytes, and apply voltage for electrolytic assisted leaching. The electrochemical purification method of the present invention can solve the problem that the prior art removes impurities in natural graphite, the leaching reagent is highly toxic and corrosive, and it is easy to pollute the environment, and the fixed carbon content of the purified graphite is less than 99.9%, which is difficult to be further applied to the field of lithium ion batteries. The amount of hydrofluoric acid used in the present application method is reduced by 50% compared with the traditional hydrofluoric acid method for purifying natural graphite, which is beneficial to environmental protection. The method has low preparation cost, simple operation method, low energy consumption, is easy to prepare on a large scale, and the purity of the purified graphite product is as high as 99.9% or more, which can be applied to the field of negative electrode materials for lithium ion batteries.
[0031] The present invention will be further described below in conjunction with specific embodiments.
[0032] Example 1
[0033] The dried spherical graphite tailings were dispersed in a hydrochloric acid solution at a solid-liquid ratio of 1:5 to form a suspension, and ultrasonic-assisted leaching was performed for 3 hours; the suspension was filtered, the graphite samples after acid leaching were collected for drying, and the dried graphite samples were pressed into sheets; the obtained graphite samples were electrolyzed at an electrolysis temperature of 20°C, a solid-liquid ratio of the graphite sample to the electrolyte of 1:4, wherein the ratio of hydrofluoric acid to the graphite sample was 1.5:1, and the electrolysis reaction time was 150 minutes. After the electrolysis, the electrolyte and the graphite sample were filtered and decomposed, and the graphite sample was collected and dried to obtain a high-purity natural graphite material. The purity of the high-purity graphite was measured to be 99.913% according to the graphite chemical analysis method of GB / T 3521-2008.
[0034] Example 2
[0035] The dried spherical graphite tailings were dispersed in a hydrochloric acid solution at a solid-liquid ratio of 1:5 to form a suspension, and ultrasonic-assisted leaching was performed for 3 hours; the suspension was filtered, the graphite sample after acid leaching was collected for drying, and the dried graphite sample was pressed into sheets; the obtained graphite sample was electrolyzed at an electrolysis temperature of 20°C, a solid-liquid ratio of the graphite sample to the electrolyte of 1:4, wherein the ratio of hydrofluoric acid to the graphite sample was 1.25:1, and the electrolysis reaction time was 100 minutes. After the electrolysis, the electrolyte and the graphite sample were filtered and decomposed, and the graphite sample was collected and dried to obtain a high-purity natural graphite material. The purity of the high-purity graphite was measured to be 99.930% according to the graphite chemical analysis method of GB / T 3521-2008.
[0036] Example 3
[0037] The dried spherical graphite tailings were dispersed in a hydrochloric acid solution at a solid-liquid ratio of 1:5 to form a suspension, and ultrasonic-assisted leaching was performed for 3 hours; the suspension was filtered, the graphite samples after acid leaching were collected for drying, and the dried graphite samples were pressed into sheets; the obtained graphite samples were electrolyzed at an electrolysis temperature of 20°C, a solid-liquid ratio of the graphite sample to the electrolyte of 1:4, wherein the ratio of hydrofluoric acid to the graphite sample was 1:1, and the electrolysis reaction time was 100 minutes. After the electrolysis, the electrolyte and the graphite sample were filtered and decomposed, and the graphite sample was collected and dried to obtain a high-purity natural graphite material. The purity of the high-purity graphite was measured to be 99.941% according to the graphite chemical analysis method of GB / T 3521-2008.
[0038] Example 4
[0039] The dried spherical graphite tailings were dispersed in a hydrochloric acid solution at a solid-liquid ratio of 1:5 to form a suspension, and ultrasonic-assisted leaching was performed for 3 hours; the suspension was filtered, the graphite sample after acid leaching was collected for drying, and the dried graphite sample was pressed into sheets; the obtained graphite sample was electrolyzed at an electrolysis temperature of 20°C, a solid-liquid ratio of the graphite sample to the electrolyte of 1:4, wherein the ratio of hydrofluoric acid to the graphite sample was 0.75:1, and the electrolysis reaction time was 100 minutes. After the electrolysis, the electrolyte and the graphite sample were filtered and decomposed, and the graphite sample was collected and dried to obtain a high-purity natural graphite material. The purity of the high-purity graphite was measured to be 99.950% according to the graphite chemical analysis method of GB / T 3521-2008.
[0040] Example 5
[0041] The dried spherical graphite tailings were dispersed in a hydrochloric acid solution at a solid-liquid ratio of 1:5 to form a suspension, and ultrasonic-assisted leaching was performed for 3 hours; the suspension was filtered, the graphite sample after acid leaching was collected for drying, and the dried graphite sample was pressed into sheets; the obtained graphite sample was electrolyzed at an electrolysis temperature of 20°C, a solid-liquid ratio of the graphite sample to the electrolyte of 1:4, wherein the ratio of hydrofluoric acid to the graphite sample was 0.50:1, and the electrolysis reaction time was 100 minutes. After the electrolysis, the electrolyte and the graphite sample were filtered and decomposed, and the graphite sample was collected and dried to obtain a high-purity natural graphite material. The purity of the high-purity graphite was measured to be 99.904% according to the graphite chemical analysis method of GB / T 3521-2008.
[0042] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for electrochemical purification of natural graphite spherical tailings, characterized in that: The following steps are involved: Step 1, dispersing the dried natural graphite spherical tailings in a solvent consisting of deionized water and acid at a certain solid-liquid ratio to form a suspension, and subjecting the suspension to an ultrasonic-assisted acid leaching treatment for a certain period of time; Step 2, filtering the suspension, collecting the graphite sample after acid leaching, drying the graphite sample, and then pressing the dried graphite sample into sheets; Step 3, electrolyzing the graphite sample obtained in step 2, wherein the electrolyte is a mixed solution composed of hydrofluoric acid, sulfuric acid and deionized water. After the electrolysis is completed, filtering and separating the electrolyte and the graphite sample is performed, and then the graphite sample is dried, and finally the dried graphite sample is subjected to quality inspection.
2. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that, The particle size of the natural graphite spherical tailings used in step 1 is 5 to 15 μm.
3. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that, In the step 1, the solid-liquid ratio of the natural graphite spherical tailings to the solution is one of 1:4, 1:5 and 1:
6.
4. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that, In step 1, the acid of the solvent is one of hydrochloric acid, hydrofluoric acid and sulfuric acid, or a mixture of two or more thereof, and the ratio of the acid to deionized water is one of 1:1, 1:2 and 2:
3.
5. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that: In step 1, the ultrasonic-assisted acid leaching time is 4 to 8 hours and the temperature is 40 to 70° C.
6. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that: In the step 2, the pressure for forming the graphite sample into sheets is 30 MPa, and the diameter of the graphite sheet after forming is 1.8 cm.
7. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that: The ratio of hydrofluoric acid, sulfuric acid and deionized water in the electrolyte used in step 3 is (3-6): (5-8): (26-32).
8. A method for electrochemical purification of natural graphite spherical tailings according to claim 1, characterized in that: The electrolysis temperature in step 3 is 20° C. to 90° C., the solid-liquid ratio of the graphite sample to the electrolyte is 1:(10-4), and the electrolysis time is 2-12 hours.